Laboratory evaluation of shear bond strength of porcelain repair methods - Abdolhamid Alhavaz; Vahid Soltankarimi; Pouya Aslani (Babol University of Medical Sciences, 2012)
Introduction: Porcelain fracture is a relatively common problem in clinical dental practice. Various methods have been proposed for repairing porcelain fractures including direct composite resin repair or construction of a porcelain laminate veneer and its cementation with a resin cement. Evaluation of shear bond strength of porcelain repair methods was the purpose of this study. Methods: Twenty feldspathic porcelain discs (10 mm in diameter) were fabricated. The samples underwent air-born abrasion with an aluminum oxide and etching with HF, and were then ultrasonically cleaned and randomized into two groups: 1- repair with porcelain disc (7 mm in diameter) with light cure cement (Choice 2) and 2- repair with resin composite (Clearfil AP-X). We measured the shear bond strength of the samples by Zwick Roll at 0.5 mm/min crosshead speed.  Results: The resin composite group had the highest shear bond strength (12.91 MPa). We found no significant differences between the choice and composite groups (p=0.970). Conclusions: Our findings indicate that resin composite yields acceptable shear bond strength to be used in porcelain repair.